All‐Dielectric Frequency Selective Surface Based on 3D Printing Materials. Issue 14 (21st May 2018) - Li, Liyang; Wang, Jun; Feng, Mingde; Du, Hongliang; Ma, Hua; Wang, Jiafu; Zhang, Jieqiu; Qu, Shaobo
Abstract : In this paper, the authors demonstrate a method of using low permittivity 3D printing materials to design all‐dielectric frequency selective surface (FSS). The 3D printing method can be used to fabricate complex structures rapidly and freely. The relative permittivity of materials used in 3D printing is in the range of ≈2.5–4.5. These low permittivity materials are usually transparent to the electromagnetic (EM) waves. In this paper, these low permittivity materials are used to realize stop band FSS to inspire the localized enhanced electric resonances and magnetic resonances by the periodic design. With the ability of using different dielectric materials with low permittivity, FSS with more functional effects may be designed and fabricated in an inexpensive and bio‐friendly way. Abstract : 3D Printing all‐dielectric frequency selective surface (FSS) is proposed and fabricated. Microwave transparent low permittivity materials can be used to realize bandstop FSS. 3D printing method promotes a rapid fabrication of FSS in flexible shapes and large scales. Future studies in different low permittivity dielectric materials may capable to support flexible design of multi‐functional FSS.